PENCEGAHAN KEKERASAN SEKSUAL PADA ANAK MELALUI PENGAJARAN PERSONAL SAFETY SKILLS - Mashudi, Esya Anesty; Nur' aini, Nur' aini (Universitas Pendidikan Indonesia, 2015)
The increasingly widespread phenomenon of children sexual abuselead to intervention and prevention efforts in overcome the malicious effects ofsexual abuse against children. Various ideas have been triggered mental healthexperts, in order to prevent the occurrence of sexual abuse against children. Oneof many efforts that praised by international community is teaching personalsafety skills to children, this method was popularized by Bagley and King in 2004.Personal safety skills are a set of skills that need to be owned by children, so thatthey can refrain themselves from perpetrators of sexual abuse and the situationsthat allow sexual abuse, children are also taught to recognize the sensitive partsof their body, how to maintain personal limbs of another person touches thatmake them uncomfortable, and reported perpetrators of sexual abuse to trustedadult. This paper aims to explain the phenomenon of sexual abuse againstchildren, and how the prevention of children sexual abuse can be done throughteaching personal safety skills. Children with personal safety skills have a strongtendency to recognize, resist and report the situations that allow sexual abuse.